Effect of spray volume, application timing and droplet size on spray distribution and control efficacy of different fungicides against circular leaf spot of persimmon caused by Plurivorosphaerella nawae - Garcerá, Cruz; Vicent, Antonio; Chueca, Patricia (Elsevier, 2020)
In recent years, Spain has been the scenario of the largest production growth of persimmon worldwide. However, circular leaf spot of persimmon, caused by Plurivorosphaerella nawae, was responsible for causing severe yield and economic losses. This work studied the effect of spray volume rate, droplet size, and application timing on spray distribution and disease control efficacy for mancozeb, pyraclostrobin and difenoconazole applications. Also fungicide degradation dynamics on persimmon leaves were studied. A method to inoculate persimmon plants using natural inoculum of P. nawae was developed. Results showed that spray volume influenced canopy spray coverage regardless of the fungicide used, but it did not influence disease control efficacy, except when pyraclostrobin was applied as pre-inoculation spray. Pyraclostrobin also showed a good post-inoculation activity. Influence of droplet size on spray coverage depended on the leaf side considered but it did not affect disease control efficacy except for pyraclostrobin applied 14 days after inoculation, when coarse droplets had lower control than fine ones. In general, slight degradation dynamics of fungicide residues on leaves were observed at 14 days.